Current use of androgens in bone marrow failure disorders: a report from the Severe Aplastic Anemia Working Party of the European Society for Blood and Marrow Transplantation - Pagliuca, Simona; Kulasekararaj, Austin G.; Eikema, Dirk-Jan; Piepenbroek, Brian; Iftikhar, Raheel; Satti, Tariq Mahmood; Griffin, Morag; Laurino, Marica; Kupesiz, Alphan; Bertrand, Yves; Fattizzo, Bruno; Yakoub-Agha, Ibrahim; et al. (Haematologica, 2024)
Androgens represent the historical therapeutic backbone of bone marrow failure (BMF) syndromes. However, their role has rarely been analyzed in a prospective setting, and systematic and long-term data regarding their usage, effectiveness and toxicity in both acquired and inherited BMF are currently unavailable. Here, taking advantage of a unique disease-specific international dataset, we retrospectively analyzed the largest cohort so far of BMF patients who received androgens before or in the absence of an allogeneic hematopoietic cell transplantation (HCT), re-evaluating their current use in these disorders. We identified 274 patients across 82 European Society for Blood and Marrow Transplantation (EBMT) affiliated centers: 193 with acquired (median age 32 years) and 81 with inherited (median age 8 years) BMF. With a median duration of androgen treatment of 5.6 and 20 months, respectively, complete and partial remission rates at 3 months were 6% and 29% in acquired and 8% and 29% in inherited disorders. Five-year overall survival and failure-free survival (FFS) were respectively 63% and 23% in acquired and 78% and 14% in inherited BMF. Androgen initiation after second-line treatments for acquired BMF, and after >12 months post diagnosis for inherited BMF were identified as factors associated with improved FFS in multivariable analysis. Androgen use was associated with a manageable incidence of organ-specific toxicity, and low rates of solid and hematologic malignancies. Sub-analysis of transplant-related outcomes after exposure to these compounds showed probabilities of survival and complications similar to other transplanted BMF cohorts. This study delivers a unique opportunity to track androgen use in BMF syndromes and represents the basis for general recommendations on this category of therapeutics on behalf of the Severe Aplastic Anemia Working Party of the EBMT.